MEKANISMEPASAR SEBAGAI PENENTU HARGA (ANALISIS PEMIKIRAN IBN TAIMIYAH) - Sri Sudiarti (Universitas Islam Negeri Sumatera Utara, 2015)
In the perspective of the Islamic concept of the price is not much different from the modern economy. But in Islam has always emphasized the role of ethics (moral values). Basically, Islam has been described that a fair price is the price established by the market forces that run freely, the meeting between the forces of demand and supply. The concept of the proposed price of IbnTaymiyya is not much different from what has been formulated by modern economists. The only difference is the emphasis on ethics and morals. In principle, fair prices occurs when the demand and supply of naturally occurring and balanced (equilibrium price). A fair price according to IbnTaymiyya is the value of the price of goods which the seller sells his wares and generally accepted as being commensurate with the goods sold or other similar goods in a particular place and time. IbnTaymiyyah and very modern economists agree that if the government does not interfere in the determination of prices during a market mechanism walk naturally without any disturbances from the traders and from the buyer.